Excessive and Problematic Internet Use During the Coronavirus Disease 2019 School Closure: Comparison Between Japanese Youth With and Without Autism Spectrum Disorder - Kentaro Kawabe; Kentaro Kawabe; Rie Hosokawa; Rie Hosokawa; Kiwamu Nakachi; Kiwamu Nakachi; Ayumi Yoshino; Ayumi Yoshino; Fumie Horiuchi; Fumie Horiuchi; Shu-ichi Ueno (Frontiers Media S.A., 2020)
Internet use in the youth has increased manifold during the coronavirus disease 2019 (COVID-19) pandemic. Individuals with autism spectrum disorder (ASD) generally have a higher risk of problematic internet use. The aim of this study is to investigate the differences in internet and related digital media use between children with ASD and their typically developing counterparts during the COVID-19 pandemic. In this online survey in Japan conducted from April 30 to May 8, 2020, we analyzed digital media time of 84 children with ASD and 361 age- and gender-matched controls before and after school closure. Digital media use duration was significantly longer in the ASD group than in the control group before the pandemic. The increase of media use time was more prominent in the control group than in the ASD group. We observed excessive Internet use among children with ASD and without ASD, especially during the COVID-19 pandemic. It is necessary to establish strategies to prevent excessive internet use in not only children and adolescents with ASD but also without ASD in the post-pandemic world.